Factors affecting the participation and utilization of breast cancer screening services among health care workers Kolar: a qualitative study - Swathi, Hogarehalli Jayanna; Vinayaka, Hogarehalli Jayanna; Mokhasi, Varsha R.; Bhanuprasad, Byrappa Nirmala (International Journal Of Community Medicine And Public Health, 2024)
Background: India is going through epidemiologic transition with a shift of disease burden from communicable to non-communicable diseases. There is no organized screening programme for breast cancer in the country. Hence, a large proportion of women with cancer of the breast present in advanced stages of cancer. The integrated cancer control programme calls for early detection of cancer, opportunistic screening and cancer outreach camps that are to be promoted and carried out by health care providers. The objective of this study was thus designed to understand the various factors preventing the participation and utilisation of breast cancer screening. Methods: It was a qualitative method with two groups. The study was conducted between two taluks out of 6, Kolar and Bangarpete. All Angawadi workers and helpers aged more than 30 years were invited and those who have history of breast cancer and family history of breast cancer were excluded from the study. All the subjects who did not attend the screening were included to elicit the reasons for non-attendance. Results: The theme ‘barriers to screening uptake’ were broadly divided into three main categories- namely ‘worry’, ‘transport’ and ‘work commitment’. The sub-category ‘anxiety’ (31.9%) was reported to be the highest barrier and least was in the sub-category ‘no replacement’ (4.3%). The frequency of response categorized into different sub-categories. Conclusions: The reasons were identified by using ‘single question’ interview guide, and were categorized into ‘worry’, ‘transport’ and ‘work-commitment’. Barrier in ‘worry’ category was found to be highest.